Comprobación del efecto cicatrizante de Peperomia scutellaefolia R et P. aspectos botánicos, químicos y farmacológicos - Guillermo, Ruth F. (2005)
A description of the morphological external characteristics of Peperomia scutellaefolia R. et P. and some microscope details and the wound healing effect of vegetal specie Peperomia scutellaefolia R. et P. were evaluated and described in this research using tensiometric methods and the results were corroborated with histological studies in order to observe and analyze the histological evolution in each case. Batch Balb C 53 albine mice with 25g of average weight were used and treated with Carbopol 940 gel s with 5%, 10%, 20% and 30% W /W concentrations of this vegetal extract. The results obtained were compared with two groups: the control group (without treatment) and another group treated with a commercial medicament. A better wound healing cffect with Peperomia' s 5% W /W concentration gel was obtained. Flavonoids and fenolic compounds were found and identified by ultraviolet and infrared spectrophotometry and coloration reactions.